Analysis of Small Medium Enterprises Export Inhibiting Factors Subsector Teak Craft Industries in Blora Regency - Inung - Rosmarinda; Karnowahadi - Karnowahadi; Subandi - Subandi (Admisi dan Bisnis, 2021)
The export development of SMEs was faced with various obstacles that could hinder Small Medium Enterprises (SMEs) from exporting. These obstacles could come from internal and external SMEs. The purpose of this study is to analyze the effect of Knowledge Barrier (KB), Resource Barrier (RB), Procedure Barrier (PB), and Exogenous Barrier (EB) on Export Barriers (HE) for SMEs in the teak craft industry subsector in Blora Regency both partially or simultaneously. This research is quantitative study using observational data methods, questionnaires, and literature studies. The number of samples was 43 respondents who have been experienced in export activities. This study used multiple linear regression analysis.The results show that the coefficient of determination (R2) in this study shows the influence of the variable Knowledge Barrier (KB), Resource Barrier (RB), Procedure Barrier (PB), and Exogenous Barrier (EB) on Export Barriers by 61.7%, while the remaining 39.3 % evidence by other variables not present in this study. Meanwhile, the results of the F test show that simultaneously the variables of KB, RB, PB, EB have a significant affect on Export Barrier. Furthermore, partially, KB and PB variables affect but not significantly on export barriers. Meanwhile, the regression equation for the variables KB, RB, PB, EB was HE = 0.017 - 0.046KB + 0.299RB - 0.110PB + 0.688EB. Based on the results of the study, from the four variables studied, the Exogenous Barrier (EB) variable was the most dominant variable affect the export barriers to SMEs in the teak craft industry subsector in Blora Regency